The reception of international law in the European Court of Human Rights - Forowicz, Magdalena (Oxford : Oxford University Press, 2010)
The European Court of Human Rights increasingly refers to international law in its case law, but its interpretation of it is often problematic. This book examines whether the Court has been able to create a coherent approach to the evaluation of international law and, ultimately, whether it has been able to contribute to its development.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Court of Human Rights; Human rights -- Europe; International and municipal law -- Europe